Viral infections: Brief review and prevention from Islamic perspectives - E. Zainudin, Engku Nuraishah Huda; May, Khin Soe; Izzati, Amni; Yusof, Nurul Asyiqin (Malaysian Journal of Medicine and Health Sciences, 2021)
Introduction: The magnitude of diseases caused by viral pathogens is enormous. Some types of virus frequently leading to chronic infections which cause significant medical and economic issues. Viral agents are constantly emerging or re-emerging with the recent Coronavirus outbreak causing panic to the people worldwide. Methodology: Relevant literatures were reviewed based on a combination of one or more of the following keywords: infection, viral diseases, modes of transmission, prevention control. Islamic perspective related to the topic was extracted using the primary sources (related Qur’anic verses and Hadith) as well as secondary sources (fatwa; Islamic jurisprudence, made by Islamic scholars). Results: This review focuses on an intelligible framework that highlights the differences between various modes of viral transmission and prevention. Conclusion: Understanding viral modes of transmission and prevention methods may allow for improved surveillance and prevention measures. This review also demonstrates prevention methods from Islamic beliefs in order to control future occurrence of disease outbreaks. Another major outcome of this review would allow various parties. i.e. students, university, the community, health scientists, medical practitioners to be cognizant pertaining viral infection.